Theoretical analysis of anomalous explosion behavior for H2/CO/O2/N2 and CH4/O2/N2/CO2 mixtures in the light of combustion-induced rapid phase transition. (6th July 2015) - Basco, Anna; Cammarota, Francesco; Di Sarli, Valeria; Salzano, Ernesto; Di Benedetto, Almerinda
Abstract Oxidation of solid, liquid and gaseous fuels either in pure oxygen or in oxygen-enriched atmosphere is surely attractive in the worldwide challenge for zero emission technology and in chemical process intensification. However, this opportunity raises several issues not only in terms of costs, but also in terms of safety. Indeed, in the case of loss of control, explosion consequences can be dramatic. Moreover, deflagration and detonation can be accompanied by a new explosion regime, at least under some specific conditions of mixture composition, characterized by strong oscillations in measured pressure time histories that culminate in over-adiabatic peaks (i.e., values of the peak pressure higher than the thermodynamic value). This anomalous behavior has been called heat explosion by BASF researchers and combustion-induced Rapid Phase Transition (cRPT) by the current authors, but questions about its nature and occurrence are still open. In this work, a theoretical analysis was performed of anomalous explosion behavior for H2/CO/O2/N2 and CH4/O2/N2/CO2 mixtures. In particular, a criterion has been developed that allows to distinguish cRPT, in both forms of incipient and fully developed phenomenon, from deflagration and detonation. The developed criterion, based on the evaluation of a characteristic time ratio (water condensation time/reaction time), has been validated using our experimental data and BASF experimental data. It has been found that the anomalous behavior observed by BASF researchers can be successfully interpreted in the light of cRPT. An updated explosion classification, which includes cRPT, has also been proposed.